2010
DOI: 10.1007/s00540-010-0874-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tracheal intubation by the Macintosh laryngoscope and Pentax-AWS (Airway Scope) during chest compression: a manikin study

Abstract: To compare tracheal intubation with the Pentax Airway Scope (AWS) and the Macintosh laryngoscope (McL) during chest compression, 25 anesthesiologists (including 12 specialists having >5 years of experience and 13 trainees having <2 years of experience) performed tracheal intubation using either the McL or the AWS, with or without chest compression, on a manikin. Using the McL, both specialists and trainees took a significantly longer time (P < 0.01) to secure the airway with chest compression (17.3 +/- 3.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…However, marked delays in intubation during chest compression have been reported in some studies with the Macintosh laryngoscope. 9 Moreover, overall success rates were significantly lower with the Macintosh laryngoscope than with the Pentax-AWS. 7,8,10 Success rates of 100% have been reported for the Pentax-AWS compared with success rates of 57.1%, 8 74.3%, 10 and 81.3% 7 reported for the Macintosh.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, marked delays in intubation during chest compression have been reported in some studies with the Macintosh laryngoscope. 9 Moreover, overall success rates were significantly lower with the Macintosh laryngoscope than with the Pentax-AWS. 7,8,10 Success rates of 100% have been reported for the Pentax-AWS compared with success rates of 57.1%, 8 74.3%, 10 and 81.3% 7 reported for the Macintosh.…”
Section: Discussionmentioning
confidence: 95%
“…[7][8][9][10][14][15][16] The laryngoscopes employed in the majority of these previous studies were the conventional Macintosh laryngoscope and the Pentax-AWS. [7][8][9][10]14,15 While four studies [7][8][9][10] reported that the Pentax-AWS was more effective than the Macintosh laryngoscope, two studies 14,15 reported no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In simulation studies utilizing a manikin, we and others have previously reported that AWS more effectively secures the airway during chest compression simulation in a manikin than the Macintosh laryngoscope (McL) [10,11]. One group reported that AWS was superior to ATQ and McL [12].…”
Section: Introductionmentioning
confidence: 95%